Mapping evaporation and estimation of surface control of evaporation using remotely sensed land surface temperature from a constellation of satellites. Issue 2 (25th February 2013) - Bateni, S. M.; Entekhabi, D.; Castelli, F.
Key Points LST is assimilated to heat diffusion equation to estimate evaporation. Evaporation estimations are used to study the surface control on evaporation. Dependence of EF‐soil moisture relationship on vegetation cover is examined.